CLIL implemented and scaffolded in an EFL higher education context: Engineering research methodology course - Kanoksilapatham, Budsaba; Khamkhien, Attapol (Indonesian Journal of Applied Linguistics, 2022)
The increasing global and local demands to improve English proficiency have been a burgeoning challenge across the entire paradigm and domains. Specifically, in academia, the ability to read English research articles is of paramount importance. Meanwhile, Content Language Integrated Learning (CLIL) implementation has been recognized to be a successful teaching approach. This study aims to estimate the CLIL impact on enhancing the studentsâ€™ English research article reading skills, enlarging their vocabulary repertoire, and boosting the studentsâ€™ and instructorsâ€™ satisfaction. The focus of the study is on a â€œresearch methodologyâ€ course for engineering students in Thailand. Throughout CLIL, the language teachers and engineering teachers closely collaborated, designing course materials and developing language activities. To assess research article reading skills and vocabulary knowledge, two sets of similar pretests/posttests were administered. Then, to assess the studentsâ€™ level of CLIL satisfaction, questionnaires were completed, and two separate focus group discussion sessions were conducted with the students and teachers. Test score analysis yielded a significantly enhanced output in both the content subject and English vocabulary knowledge. Additionally, questionnaire and focus group discussion data analysis indicated that both the students and teachers had positive attitudes toward CLIL instruction. Taken together, this study demonstrates that to achieve full optimization of CLIL benefits, scaffolding needs to be supplemented to accommodate individual learning contexts.Â